2023
DOI: 10.3390/life13040946
|View full text |Cite
|
Sign up to set email alerts
|

Aiding Cancer’s “Sweet Tooth”: Role of Hexokinases in Metabolic Reprogramming

Abstract: Hexokinases (HKs) convert hexose sugars to hexose-6-phosphate, thus trapping them inside cells to meet the synthetic and energetic demands. HKs participate in various standard and altered physiological processes, including cancer, primarily through the reprogramming of cellular metabolism. Four canonical HKs have been identified with different expression patterns across tissues. HKs 1–3 play a role in glucose utilization, whereas HK 4 (glucokinase, GCK) also acts as a glucose sensor. Recently, a novel fifth HK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 166 publications
(330 reference statements)
0
6
0
Order By: Relevance
“…Hexokinases carry out the phosphorylation of glucose and we wanted to learn if BKIDCs were dependent on a specific isoform of hexokinase (HK). Among five isoforms of hexokinases expressed in humans (HK1, HK2, HK3, GCK1/HK4, and HKDC1)(56), HK1 and HK2 are reportedly predominant in LNCaP cells(57). We used a CRISPR-Cas9 system to generate HK1 and HK2 knock-out (KO) LNCaP clones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hexokinases carry out the phosphorylation of glucose and we wanted to learn if BKIDCs were dependent on a specific isoform of hexokinase (HK). Among five isoforms of hexokinases expressed in humans (HK1, HK2, HK3, GCK1/HK4, and HKDC1)(56), HK1 and HK2 are reportedly predominant in LNCaP cells(57). We used a CRISPR-Cas9 system to generate HK1 and HK2 knock-out (KO) LNCaP clones.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple enzymatic isoforms can also perform overlapping functions, and metabolic flexibility can divert processes away from inhibited pathways. Mammals possess five HK isoenzymes, including HK1, HK2, HK3, HK4/GCK1, and HKDC1 with overlapping and specific tissue and cellular distribution patterns to fix glucose as the first step in glycolysis (56). Along with catalytic domains, HK1 and HK2 contain Nterminal motifs to interact with VDAC1 for association with mitochondria and the glucose-6-phosphate (G6P)-binding sties for feedback allosteric inhibition (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HKs are the first rate-limiting enzymes involved in glycolysis, which phosphorylate glucose, thus trapping it inside the cells. 16 Five HK isozymes (HK1-4 and HKDC1) have been identified in humans with diverse tissue distribution and enzyme kinetics. HK4, commonly known as glucokinase, is the predominant HK isozyme of hepatocytes.…”
Section: Glycolysismentioning
confidence: 99%
“…Subsequent studies found that HKDC1 is significantly upregulated and is a protumorigenic player in HCC and other cancers (11-14). Its impact on glucose update of cancer cells and the subcellular association with mitochondria-associated membranes have also been demonstrated (15). What remains unexplored are the potential differences of HKDC1 compared to the other upregulated HKs regarding their lineage specificity and metabolic activity in HCC since HCC is well known for its complex tumor microenvironment (TME) which consists of various cell types with different functions and metabolic needs.…”
Section: Introductionmentioning
confidence: 99%